Short Communication Cis and Trans Monoenoic Fatty Acids of Hydrogenated Mango Kernel Fats (Biological Sciences - PJSIR, 2007)
The fats prod uced as a resul t of hydrogenation of the oi ls of three varieties of mango kernel ( Mangi(erai11d ica),  We re fou n d tO COn Si St Of / rans  fatty acids, C    ,    (0. 02-0.60 o/o) , CIM: I  (2. 69-4.48 o/o) ,ClO : I  (0.02-0. 04 o/o) , C    ,16 1(traces-0.05 %), C2 ,. 1  ( traces-0.02 %) i n  add i ti on  to cis  fa t ty acid s.